Three perfect liars : a novel - Perks, Heidi, 1973- (Gallery Books, 2020)
"From the author of Her One Mistake, hailed as "chilling, captivating" by New York Times bestselling author Megan Miranda, comes a riveting new suspense novel about three ambitious women whose lives are turned upside down in the aftermath of a horrifying fire, which destroys a successful advertising agency and threatens to expose a tangled web of lies. Laura has returned to work at Morris and Wood after her maternity leave, only to discover that the woman she brought in to cover for her isn't planning on going anywhere. Despite her close relationship with the agency's powerful CEO, Harry Wood, she feels sidelined-and outmaneuvered-as she struggles to balance the twin demands of work and motherhood. Mia was only supposed to be a temporary hire at Morris and Wood, but she's managed to make herself indispensable to everyone. Everyone, that is, except Laura. If people only knew why she was so desperate to keep her job, they might not want her to stay. Janie gave up everything to support her husband and the successful agency he runs. But she has her own dark secret to protect...and will go to any lengths to keep it safe. With signature prose lauded as "breathtaking" and "bone-chilling" by USA TODAY bestselling author Cristina Alger and plenty of shocking twists and turns, Three Perfect Liars is an unputdownable thriller for fans of Watching You and The Couple Next Door"--